2020
DOI: 10.1212/nxg.0000000000000505
|View full text |Cite
|
Sign up to set email alerts
|

Intragenic variants in the SMN1 gene determine the clinical phenotype in 5q spinal muscular atrophy

Abstract: ObjectiveThe aim of the study was to report the proportion of homozygous and compound heterozygous variants in the survival motor neuron 1 (SMN1) gene in a large population of patients with spinal muscular atrophy (SMA) and to correlate the severity of the disease with the presence of specific intragenic variants in SMN1 and with the SMN2 copy number.MethodsFour hundred fifty Brazilian patients with SMA were included in a retrospective study, and clinical data were analyzed compared with genetic data; the SMN2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 25 publications
1
18
1
1
Order By: Relevance
“…More surprisingly, 2 patients with a c.5C > T mutation (p.Ala2Val) in SMN1 showed phenotype type 3. There was a report of similar cases with a different mutation at the same location, c.5C > G (p.Ala2Gly) in SMN1, who presented with phenotype type 3 in spite of carrying only a single copy of SMN2 [27]. These findings, including ours, suggested that SMN1 with missense mutations, c.5C > T or c.5C > G, may produce SMN proteins with some function (hypomorphic mutation or leaky mutation).…”
Section: Relationship Between Clinical Phenotype and Smn2 Copy Numbersupporting
confidence: 63%
“…More surprisingly, 2 patients with a c.5C > T mutation (p.Ala2Val) in SMN1 showed phenotype type 3. There was a report of similar cases with a different mutation at the same location, c.5C > G (p.Ala2Gly) in SMN1, who presented with phenotype type 3 in spite of carrying only a single copy of SMN2 [27]. These findings, including ours, suggested that SMN1 with missense mutations, c.5C > T or c.5C > G, may produce SMN proteins with some function (hypomorphic mutation or leaky mutation).…”
Section: Relationship Between Clinical Phenotype and Smn2 Copy Numbersupporting
confidence: 63%
“…Mendonca et al recently identified 16 patients with the exon 3 nonsense mutation c.460C>T (p.Gln154*). 16 All of the patients presented with a milder phenotype (SMA types 3 and 4), including 2 patients with 1 SMN2 copy and 10 patients with 2 SMN2 copies. The missense mutation p.Ala2Val has been found in several type 3 patients in the presence of 1 or 2 copies of SMN2 while type 1 patients with p.Trp92Ser were shown to have 3 SMN2 copies.…”
Section: Genotype Phenotype Associationmentioning
confidence: 97%
“…Recurrent variants have been found in exons 3 and 6, making these two exons hot spots for small mutations and missense mutations, respectively ( Figure 2D ). 15 , 16 Exon 6 codes for a domain in the protein which plays a role in protein oligomerization, and those patients with exon 6 missense mutations have decreased SMN protein self-oligomerization capacity. 15 The exon 6 p.Tyr272Cys missense mutation is the most frequently reported mutation in the SMN1 gene.…”
Section: Pathogenic Variantsmentioning
confidence: 99%
“…In addition, some missense variants in exon 1 of SMN1 are associated with a milder phenotype [44]. Two recurrent variants are c.5C>T (p.Ala2Val) and c.5C>G (p.Ala2Gly), which are considered hypomorphic alleles identified in SMA type III patients [51,52]. In fact, it has been shown in a SMA mouse model that the change p.Ala2Gly does not produce total loss of protein function [53] and no significant decrease of full-length SMN1 transcripts [43].…”
Section: The Known Validated Genotypesmentioning
confidence: 99%